Quantitative computed tomography predicts outcomes in idiopathic pulmonary fibrosis. Issue 12 (25th July 2022) - Humphries, Stephen M.; Mackintosh, John A.; Jo, Helen E.; Walsh, Simon L. F.; Silva, Mario; Calandriello, Lucio; Chapman, Sally; Ellis, Samantha; Glaspole, Ian; Goh, Nicole; Grainge, Christopher; Hopkins, Peter M. A.; et al.
Abstract: Background and objective: Prediction of disease course in patients with progressive pulmonary fibrosis remains challenging. The purpose of this study was to assess the prognostic value of lung fibrosis extent quantified at computed tomography (CT) using data‐driven texture analysis (DTA) in a large cohort of well‐characterized patients with idiopathic pulmonary fibrosis (IPF) enrolled in a national registry. Methods: This retrospective analysis included participants in the Australian IPF Registry with available CT between 2007 and 2016. CT scans were analysed using the DTA method to quantify the extent of lung fibrosis. Demographics, longitudinal pulmonary function and quantitative CT metrics were compared using descriptive statistics. Linear mixed models, and Cox analyses adjusted for age, gender, BMI, smoking history and treatment with anti‐fibrotics were performed to assess the relationships between baseline DTA, pulmonary function metrics and outcomes. Results: CT scans of 393 participants were analysed, 221 of which had available pulmonary function testing obtained within 90 days of CT. Linear mixed‐effect modelling showed that baseline DTA score was significantly associated with annual rate of decline in forced vital capacity and diffusing capacity of carbon monoxide. In multivariable Cox proportional hazard models, greater extent of lung fibrosis was associated with poorer transplant‐free survival (hazard ratio [HR] 1.20, p  < 0.0001) and progression‐free survival (HR 1.14, p  < 0.0001). Conclusion: In a multi‐centre observational registry of patients with IPF, the extent of fibrotic abnormality on baseline CT quantified using DTA is associated with outcomes independent of pulmonary function. Abstract : The extent of pulmonary fibrosis, measured objectively at baseline computed tomography using a deep learning algorithm, is associated with disease progression and mortality, independent of pulmonary function. See related Editorial